Strategic Management in Saudi Arabian Private Pre-University Education: A Case Study - Alenezi, Omeir (DIRASAT: EDUCATIONAL SCIENCES, 2019)
This study discussed issues of strategic management in the private pre-university context in Saudi Arabia. Private pre-universities show considerable interest in investment and entrepreneurship, but they lack such interest in academic research. This study aimed to bridge this gap. The first part of the study presented the theoretical issues in relation to strategic management with a focus on the educational sector. The second part presents an empirical case study of one private school in Riyadh. The study employed interviews, documentary analysis and researcher diaries. The findings showed a number of gaps in relation to strategic planning and management. Among these is the lack of a shared mission, visions and values. There is also a gap in understanding the key strategic issues, for example, the role of the teacher in strategic issues.